A new approach to tackle the shortcomings of food production systems: The Integrated Agri-food System Initiative (IASI) - CGIAR Research Program on Maize (2021)
The IASI methodology offers governments and development practitioners the possibility to transform food systems by scaling out innovative farming technologies enabling sustainably managed natural resources and improved nutrition/food security.